Contemporary perspectives of railway, logistics and urban development in Budapest - Péter Wolf; Bálint Kádár (Spatial and transport infrastructure development in Europe: Example of the Orient/East-Med Corridor, 2019)
Budapest metropolitan area is the major logistic hub of Hungary, as major TENT-T corridors cross the city. Growth potential is high, and railway infrastructure, brownfields and new hubs of logistics are key areas of development; still none of these sectors are at their full potential. The case study introduces the historical background and evolution of logistics and the rail network, and national objectives aiming to improve efficiency in infrastructure to foster sustainability and competitiveness. The focus areas are rail freight, offshore trade, service export, intermodal terminals, air cargo terminals, suburban passenger services and investments aiming to increase the usage of railway in freight and passenger transport. The study highlights how the region is seeking its competitive edge, and how progress is hindered by the lack of railway capacities or a lack of integrated urban planning. The urban rail concept and large brownfield sites along the lines may create opportunities for exploitation, but a lack of synergies impedes strategic development for now. – – Der Großraum Budapest ist das wichtigste logistische Zentrum Ungarns, da die wichtigsten TENT-T-Korridore die Stadt durchqueren. Das Wachstumspotenzial ist hoch, und die Eisenbahninfrastruktur, Brachflächen und neue Logistikzentren sind wichtige Entwicklungsbereiche; dennoch ist keiner dieser Sektoren voll funktionsfähig. Die Fallstudie stellt den historischen Hintergrund und die Entwicklung der Logistik und des Schienennetzes sowie nationale Ziele vor, die darauf abzielen, die Effizienz der Infrastruktur zu verbessern, um Nachhaltigkeit und Wettbewerbsfähigkeit zu fördern. Die Schwerpunkte liegen in den Bereichen Schienengüterverkehr, Offshore- Handel, Dienstleistungsexport, intermodale Terminals, Luftfrachtterminals, Personennahverkehr und Investitionen zur Steigerung der Nutzung der Schiene im Güterund Personenverkehr. Die Studie zeigt, wie die Region ihren Wettbewerbsvorteil sucht und wie der Fortschritt durch fehlende Bahnkapazitäten oder einen Mangel an integrierter Stadtplanung behindert wird. Das Stadtbahnkonzept und große Industriebrachen entlang der Trassen können Chancen zur Nutzung eröffnen, aber fehlende Synergien behindern derzeit eine erfolgreiche strategische Entwicklung.
urn:nbn:de:0156-0952134; hdl:10419/213084; https://econpapers.repec.org/RePEc:zbw:arlfob:12
Keywords: 710; logistics; transportation; spatial planning; railway development; Budapest; Logistik; Transport; Raumplanung; Eisenbahnentwicklung